1993
DOI: 10.1007/bf03172698
|View full text |Cite
|
Sign up to set email alerts
|

The social context of human learning: Some prospects for the study of socio-cognitive regulations

Abstract: Numerous studies conducted by social, cognitive, and educational psychologists suggest that learning, cognitive functioning and development, and education are fundamentally embedded in a complex social matrix. Recent studies have demonstratedthe influence on cognitive performances of several basic social variables, including evaluative pressure, group membership, situations of personal or categorical social comparison, and the academic value of the task. These findings clearly point out the necessity of consid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

1995
1995
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 55 publications
0
2
0
1
Order By: Relevance
“…One of the major findings in our previous studies (see Monteil & Huguet, 1993a, 1993b, for reviews) was that the influence of social comparison, evaluation, and performance feedback did not occur regardless of students' past academic experiences. Instead, performance change (positive vs. negative) due to the experimental manipulations systematically differed depending on the degree of consistency of these past experiences regarding the manipulations.…”
mentioning
confidence: 87%
“…One of the major findings in our previous studies (see Monteil & Huguet, 1993a, 1993b, for reviews) was that the influence of social comparison, evaluation, and performance feedback did not occur regardless of students' past academic experiences. Instead, performance change (positive vs. negative) due to the experimental manipulations systematically differed depending on the degree of consistency of these past experiences regarding the manipulations.…”
mentioning
confidence: 87%
“…This intervention is assumed to improve performance in multiple ways. It facilitates a social comparison process, which is useful to improve one's performance through direct comparison with peers (Monteil and Huguet 1999). Falk and Ichino (2006) and Mas and Moretti (2009) reported that just allowing people to observe each other's performance has a positive influence on their performance even in settings with flat wage schemes.…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%
“…Como sabemos, a partir dos anos 1970, a articulação da Psicologia do Desenvolvimento Cognitivo com a Psicologia Social enriqueceu teórica e metodologicamente a pesquisa sobre os processos de aprendizagem (Ex. : ver Monteil & Huguet, 1993) graças, sobretudo, aos estudos dos mecanismos de regulação, segundo os quais funciona o sistema didático. Essa pesquisa colocou em evidência o papel das representações sociais dos professores e dos alunos, seus meios de ação e de adaptação recíproca, assim como as variáveis sociais e institucionais que intervêm nesse sistema didático visto segundo a perspectiva da tríade professor-aluno-conteúdo a ser ensinado (Ex.…”
Section: Conceição De Maria Couto Machado Casa Thomas Jeffersonunclassified